Pan-genome analysis of three main Chinese chestnut varieties - Hu, Guanglong; Cheng, Lili; Cheng, Yunhe; Mao, Weitao; Qiao, Yanjie; Lan, Yanping (Frontiers in Plant Science, 2022)
Chinese chestnut (Castanea mollissima Blume) is one of the earliest domesticated plants of high nutritional and ecological value, yet mechanisms of C. mollissima underlying its growth and development are poorly understood. Although individual chestnut species differ greatly, the molecular basis of the formation of their characteristic traits remains unknown. Though the draft genomes of chestnut have been previously released, the pan-genome of different variety needs to be studied. We report the genome sequence of three cultivated varieties of chestnut herein, namely Hei-Shan-Zhai-7 (H7, drought-resistant variety), Yan-Hong (YH, easy-pruning variety), and Yan-Shan-Zao-Sheng (ZS, early-maturing variety), to expedite convenience and efficiency in its genetics-based breeding. We obtained three chromosome-level chestnut genome assemblies through a combination of Oxford Nanopore technology, Illumina HiSeq X, and Hi-C mapping. The final genome assemblies are 671.99 Mb (YH), 790.99 Mb (ZS), and 678.90 Mb (H7), across 12 chromosomes, with scaffold N50 sizes of 50.50 Mb (YH), 65.05 Mb (ZS), and 52.16 Mb (H7). Through the identification of homologous genes and the cluster analysis of gene families, we found that H7, YH and ZS had 159, 131, and 91 unique gene families, respectively, and there were 13,248 single-copy direct homologous genes in the three chestnut varieties. For the convenience of research, the chestnut genome database1 was constructed. Based on the results of gene family identification, the presence/absence variations (PAVs) information of the three sample genes was calculated, and a total of 2,364, 2,232, and 1,475 unique genes were identified in H7, YH and ZS, respectively. Our results suggest that the GBSS II-b gene family underwent expansion in chestnut (relative to nearest source species). Overall, we developed high-quality and well-annotated genome sequences of three C. mollissima varieties, which will facilitate clarifying the molecular mechanisms underlying important traits, and shortening the breeding process.